RANCANG BANGUN EXTERNAL ELECTROMAGNETIC RETARDERS SYSTEM PADA MOTOR 1 PHASA - Dewantara, Bima Dicky Anugrah; Manan, Saiful (Vocational School Diponegoro University, 2016)
Bima Dicky Anugrah Dewantara, Saiful Manan, in this paper explain that Electromagnetic retarders are generally known as electromagnetic inhibitors or brakes, the braking system eliminates most braking mechanics, thereby reducing conventional braking systems. Safety requirements and safety systems are developed and become a focal point of an equipment. Electromagnetic brakes are a safety component with a control system that is easy to control. With this electromagnetic brake, it will reduce maintenance costs, because it only requires a factor of electricity to be able to move it. The braking system uses electromagnetic forces to slow down a movement, which is generally a shaft motion. A dish with non-ferromagnetic metal material is attached to a rotating shaft. The disk is flanked by the side of the stator in the form of an electromagnetic coil system that can generate a magnetic field from electricity. Electric current generates a magnetic field in the coil. And the metal plate that cuts the magnetic field will cause eddy currents on the disk itself. This eddy current will generate a magnetic field whose direction is opposite to the previous magnetic field, thus inhibiting the rotary motion of the shaft. In designing, experimenting and making an External Electromagnetic Retarders System Design on 1 Phase Motor, use the NE 555 IC as the control duty cycle. So that the relationship between braking current and braking time is inversely proportional if the higher the current, the shorter the time it takes for the rotor to stop. And the relationship between braking current and motor current is directly proportional, by increasing the braking current will increase the load on the motor causing the motor current to increase.Â Keywords: Electromagnetic Retarders, Electromagnetic Brakes, Eddy Flow EffectReferencesTipler, P. 2008. Physics for Scientist volume 2. New York : WH Freeman and Company..Ishaq, M. 2007. Fisika Dasar Elektisitas dan Magnetisme. Yogyakarta: Graha Ilmu.Millman, Halkias, M.Barmawi, dan M.O.Tjia. 1971. Integrated Electronics:Analog and Digital Circuits and Systems. Jakarta : Erlangga.Ramdhani, Mohamad. 2008. Rangkaian Listrik. Jakarta : Erlangga.Bishop, Owen. 2004. Dasar-Dasar Elektronika. Jakarta : Erlangga.Halliday, David. Robert Resnick. 1978. Fisika Jilid II Edisi Ketiga. Jakarta : Erlangga